Is there a relationship between serum vaspin levels and insulin resistance in chronic renal failure? - Demir, Can; Dogantekin, Akif; Gurel, Ali; Aydin, Suleyman; Celiker, Huseyin (Professional Medical Publications, 2019)
Objective: Chronic kidney disease (CKD) patients have insulin secretion disorders and resistance to insulin effects, that is responsible for the development of cardiovascular events. Vaspin is an adipocytokine that regulates glucose and lipid metabolism. We aimed to determine the serum vaspin levels and its relationship with insulin resistance in CKD patients. Methods: In the study groups, serum vaspin levels, anthropometric parameters and routine blood tests were measured. The serum vaspin levels were examined by the enzyme-linked immunosorbent assay (ELISA) and insulin resistance was determined by the homeostasis model assessment of insulin resistance (HOMA-IR) formula. Results: The serum vaspin, HOMA-IR index and insulin levels were observed significantly high in the CKD group in comparison with the control group. No correlation was found between the serum vaspin level and the anthropometric and metabolic values. The serum vaspin level was positively correlated with the fasting plasma glucose and age but without statistical significance. Conclusion: Insulin resistance and hyperinsulinemia contribute to the development of cardiovascular complications in CKD. We consider that the increase in the serum vaspin level is a consequence of the reduced renal excretion in the CKD and increases in response to insulin resistance.
Keywords: Chronic kidney disease; Vaspin; Insulin resistance